Analysis the Influence of Brand, Offering, Relationship Equity on Learning Outcomes and their Implications for the Employability - Adevi, Isye Rahayu; Jerry Heikal (ADPEBI, 2022)
Employability refers to the achievements of graduates and their potential to obtain graduate employment. Learning outcomes are changes in behavior that occur to students on the process of adaptation or adjustment while on campus, which are expressed in the form of scores both quantitatively and qualitatively on the cognitive, affective and psychomotor indicators of students. The purpose of this study is to analyze the relationship between the influence of the Customer Equity Stack which is divided into 3 categories on Learning Outcomes with implications for Student Employability. The method in data processing uses SEM-PLS with the Second Order CFA model. The results of this study found a significant positive effect between Brand Equity and Offering Equity on Learning Outcomes. Then Brand Equity and Learning Outcomes have a significant positive effect on Employability. Meanwhile Relationship Equity has no significant effect on Learning Outcomes and Employability. In mediation, Brand Equity plays a partial mediation role on Employability, Offering Equity plays a full mediation role on Employability, and Relationship Equity does not have a mediating impact on Employability Keywords: Brand Equity, Offering Equity, Relationship Equity, Learning Outcomes, Employability